Planos individuais e coletivos de assistência à saúde: causas de extinção e manunteção compulsória do vínculo (resilição, resolução, aposentadoria e demissão) - Camasmie, Paula Villanacci Alves (2008)
The present study had the purpose of analyzing Health Care contract structures, with special attention to its legal nature and contractual network structures. Contract extinction and compulsory bond maintenance were emphasized, according to Brazilian Law #9.656/98 statements. It was also a goal of this work to discuss Health Care carriers civil responsibility for contract debts and illicit acts incurred by the professionals directly executing medical and dental care services. Several decrees were presented in this work; specially the ones originated by Tribunal de Justiça do Estado de São Paulo and Superior Tribunal de Justiça, to demonstrate legal guidances or tendencies adopted in each issue that was discussed